Space plasma physics science opportunities for the lunar orbital platform - Gateway - Dandouras, Iannis; Taylor, Matt G. G. T.; De Keyser, Johan; Futaana, Yoshifumi; Bamford, Ruth A.; Branduardi-Raymont, Graziella; Chaufray, Jean-Yves; Constantinescu, Dragos; De Angelis, Elisabetta; Devoto, Pierre; Eastwood, Jonathan; Echim, Marius; et al. (Frontiers in Astronomy and Space Sciences, 2023)
The Lunar Orbital Platform - Gateway (LOP - Gateway, or simply Gateway) is a crewed platform that will be assembled and operated in the vicinity of the Moon by NASA and international partner organizations, including ESA, starting from the mid-2020s. It will offer new opportunities for fundamental and applied scientific research. The Moon is a unique location to study the deep space plasma environment. Moreover, the lunar surface and the surface-bounded exosphere are interacting with this environment, constituting a complex multi-scale interacting system. This paper examines the opportunities provided by externally mounted payloads on the Gateway in the field of space plasma physics, heliophysics and space weather, and also examines the impact of the space environment on an inhabited platform in the vicinity of the Moon. It then presents the conceptual design of a model payload, required to perform these space plasma measurements and observations. It results that the Gateway is very well-suited for space plasma physics research. It allows a series of scientific objectives with a multi-disciplinary dimension to be addressed.